Constrained Topology Optimization of Dynamic Mechanical Systems. Issue 1 (17th December 2018) - Held, Alexander; Kohlsche, Thomas
Abstract: We present a topology optimization procedure for flexible multibody systems, which is subjected to time‐ and space‐dependent constraints. The flexible bodies are parameterized using the solid isotropic material with penalization approach. For the efficient solution of the optimization problem, the pointwise time‐dependent constraints are discretized and aggregated into a single constraint using the Kreisselmeier‐Steinhauser function. The procedure is tested by optimizing the mass of a flexible piston rod, while the deformation within the design domain is constrained.